2020
DOI: 10.31814/stce.nuce2020-14(2v)-05
|View full text |Cite
|
Sign up to set email alerts
|

Nghiên cứu thực nghiệm khả năng chịu tải trọng nén dọc trục của cột tròn bê tông cốt thép

Abstract: Ảnh hưởng của hiệu ứng bó (confinement effects) đối với ứng xử nén của cấu kiện cột bê tông cốt thép (BTCT) đã được nghiên cứu rộng rãi trên thế giới trong nhiều năm gần đây cả trên phương diện lý thuyết và thực nghiệm. Ứng dụng của hiệu ứng bó cũng đã được đưa vào một số tiêu chuẩn thi công và thiết kế kết cấu xây dựng quốc tế như tiêu chuẩn Mỹ ACI 318-19 hay Eurodoce EC2. Tuy nhiên, ở Việt Nam khái niệm này vẫn còn đang tương đối mới mẻ, đặc biệt là rất ít nghiên cứu thực nghiệm (nếu có) được công bố trong n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For lateral cyclic loading tests, the better performance of six-spiral and eleven-spiral columns than those of tied columns has been reported in previous studies even with less amount of transverse reinforcement [10,12]. In Vietnam, the use of spiral transverse reinforcement for circular columns under axial loading has just been studied by Nguyen and Pham [13]. The shear strength carried by a single-circular hoop was first derived by Ang et al [14], as shown in Fig.…”
Section: Introductionmentioning
confidence: 93%
“…For lateral cyclic loading tests, the better performance of six-spiral and eleven-spiral columns than those of tied columns has been reported in previous studies even with less amount of transverse reinforcement [10,12]. In Vietnam, the use of spiral transverse reinforcement for circular columns under axial loading has just been studied by Nguyen and Pham [13]. The shear strength carried by a single-circular hoop was first derived by Ang et al [14], as shown in Fig.…”
Section: Introductionmentioning
confidence: 93%